The tech sector and national action plans on business and human rights - Instituto Danés de Derechos Humanos; Wingfield, Richard; Tuta, Ioana; Bansal, Tulika (Copenhague: Dinamarca, 2020)
This thematic supplement is structured in three sections. The rest of Section 1 provides information on the scope of this thematic supplement, and a reflection on existing references to the tech sector in national action plans. Section 2 looks at the relationship between the tech sector and human rights, focusing on the rights to privacy, freedom of expression and equality/ non-discrimination, with an overview of the tech sector’s impacts on these rights, as well as regulatory trends. Section 3 starts by looking at how tech sector-related considerations can be included in the NAP process, with a focus on stakeholder mapping and engagement and the involvement of groups at risk.